The Literary Aspects of Internal Journeys of Imam Abdelhamid Ibn Badis (مجلة إحالات, 2026)
Travel literature, like other literary genres, is a distinctive form characterized by unique structural and narrative features that set it apart from other artistic expressions. Academic studies in this field payparticular attention to the structural dimension of the travel narrative, owing to its singularity in storytellingperformance. Accordingly, this study focuses on uncovering the artistic construction of travel writing, settingaside its circumstantial content or historical contexts. The scholar Abdelhamid Ben Badis (1889–1940) documented numerous journeys; however, thisresearch focuses specifically on his domestic travels, given the particular significance he accorded to them. In every city or village he visited, he delivered sermons, encouraging virtue, warning against vice, and advocating for unity and cooperation—always supported by verses from the Qur’an and sayings of the Prophet (peace be upon him). His journeys to Algeria’s interior cities, in particular, were marked by a striking narrative quality that lends them a literary presence more pronounced than in his other travels.